VALUE RELEVANCE OF BANK OPERATIONAL PERFORMANCE IN INDONESIA - Yulina Wong (Bina Nusantara University, 2012)
The objective of the paper is to examine the value relevance of the disclosure of bank operating performance, as regulated by Bank of Indonesia. There are five operating performance ratios (CAR, NIM, BOPO, LDR, NPL) are examined in this study. The valuation model, then, also includes earnings and market condition, as control variables. The sample firms are bank that are listed in IDX during period 2005-2010, which consists of 144 observations. The result shows that some observations had performance measures below or above Bank of Indonesia’s acceptable ratio ranges. The analysis shows that only NIM is regarded as a relevant valuation factor. CAR and BOPO are less relevant, when earnings are used as control variables. Earnings and market condition are positively related to market value of the banks. This concludes that market is indifferent in their valuation approach to banking industry and other industries.